2012
DOI: 10.1161/circulationaha.111.047274
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Remodeling in Human End-Stage Nonischemic Left Ventricular Cardiomyopathy

Abstract: Background Several arrhythmogenic mechanisms have been inferred from animal heart failure (HF) models. However, the translation of these hypotheses is difficult due to lack of functional human data. We aimed to investigate the electrophysiological substrate for arrhythmia in human end-stage non-ischemic cardiomyopathy. Methods and Results We optically mapped the coronary-perfused left ventricular wedge preparations from human hearts with end-stage non-ischemic cardiomyopathy (HF, n=10) and non-failing hearts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
143
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(163 citation statements)
references
References 58 publications
16
143
3
Order By: Relevance
“…15) Recently, it has been reported that down regulation of connexin 43 expression, reduction of connexin 43 phosphorylation, and increased fibrosis cause a conduction disorder that is likely to be a crucial component of arrhythmogenicity in human nonischemic cardiomyopathy. 16) In the present study, a decrease in expression of connexin 43 similar to that in ARVC was observed in controls, ie, HCM and DCM. However, there was no patient with sustained VT in the control group.…”
Section: Discussionsupporting
confidence: 73%
“…15) Recently, it has been reported that down regulation of connexin 43 expression, reduction of connexin 43 phosphorylation, and increased fibrosis cause a conduction disorder that is likely to be a crucial component of arrhythmogenicity in human nonischemic cardiomyopathy. 16) In the present study, a decrease in expression of connexin 43 similar to that in ARVC was observed in controls, ie, HCM and DCM. However, there was no patient with sustained VT in the control group.…”
Section: Discussionsupporting
confidence: 73%
“…Connexin-43 downregulation and lateralization, along with increased fibrous tissue content, are typical of end-stage heart failure in man and cause significant conduction abnormalities. 20 One interesting aspect of the phenotype we noticed was the regional distribution of tissue fibrosis, which was restricted to the basal regions of the heart, where it was marked ( Figure 2B). This basal localization of fibrosis has not, to our knowledge, been previously reported in other animal models of cardiomyopathy.…”
Section: Are There Specific Electrophysiological Features Of the Arrhmentioning
confidence: 85%
“…Translocation of connexin-43 to the lateral cardiomyocyte membrane was detected only in septic patients and only in a subset of these patients. Lateralization of connexin-43 is additional evidence of myocyte injury (32)(33)(34)(35). Thus, sepsis does not induce significant cardiomyocyte cell death but does induce changes consistent with mitochondrial injury and cardiomyocyte uncoupling.…”
Section: Discussionmentioning
confidence: 97%
“…Newly characterized markers of cell injury have also contributed to defining pathologic processes that mediate cell injury. Connexin-43, a critical gap junction protein that regulates cell-cell interaction and forms electrical synapses between adjacent myocytes, is involved in cellular stress responses in heart (32)(33)(34)(35). Kidney injury molecule 1 (Kim-1), a transmembrane protein expressed in damaged proximal tubular epithelial cells, is a sensitive biomarker of kidney injury (36,37).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%